2017
DOI: 10.1111/liv.13500
|View full text |Cite
|
Sign up to set email alerts
|

Decreased portal vein velocity is predictive of the development of portal vein thrombosis: A matched case‐control study

Abstract: Decreased PV velocity is associated with increased risk of future PVT. Patients with cirrhosis and decreased PV velocity are a high-risk subgroup that warrants further investigation with prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
105
3
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 34 publications
8
105
3
10
Order By: Relevance
“…slowdown of the blood flow, hypercoagulation and endothelial damage. In cirrhotic subjects various prothrombotic conditions coexist, especially coagulation alterations, while according to recent studies [2,3] the most important of all is slowdown of the portal circulation.…”
Section: Introductionmentioning
confidence: 99%
“…slowdown of the blood flow, hypercoagulation and endothelial damage. In cirrhotic subjects various prothrombotic conditions coexist, especially coagulation alterations, while according to recent studies [2,3] the most important of all is slowdown of the portal circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Results have been inconsistent. Two prospective longitudinal studies and one retrospective case control study did find a significant and independent association between baseline portal vein blood flow velocity and later development of portal vein thrombus. Another prospective study found an association on univariate analysis.…”
Section: Portal Vein Thrombosis In Patients With Cirrhosismentioning
confidence: 90%
“…Currently available epidemiological data indicate that approximately 30% of portal vein thrombi are transient . However, a systematic meta‐analysis emphasized the significant heterogeneity of the different studies analysed . The heterogeneity was probably based on several factors, including different time frames for evaluation, different selection criteria for the study population (Child‐Pugh class, hepatocellular carcinoma, waiting list for liver transplantation or control groups in of retrospective studies on anticoagulation therapy) as well as an evaluation of abstracts vs full papers …”
Section: Portal Vein Thrombosis In Patients With Cirrhosismentioning
confidence: 99%
See 1 more Smart Citation
“…PVT is associated with increased risk of hepatic decompensation and inferior overall survival in comparison with patients without PVT, and it may lead to inferior posttransplant outcomes . Many risk factors for PVT development are well established, including reduced portal vein blood flow; however, the impact of hereditary thrombophilia remains controversial . Factor V Leiden (FVL), prothrombin G20210A, and methyltetrahydrofolate reductase (MTHFR) C677T are well‐established risk factors for deep vein thrombosis (DVT) and pulmonary embolism.…”
Section: Introductionmentioning
confidence: 99%